2020
DOI: 10.1038/s41612-020-00152-9
|View full text |Cite
|
Sign up to set email alerts
|

Serial clustering of extratropical cyclones: a review of where, when and why it occurs

Abstract: Serial clustering of extratropical cyclones describes the passage of multiple cyclones over a fixed location within a given time period. Such periods often result in high precipitation totals and accumulated wind damage, leading to large societal and financial impacts. Here, we define the terminology to differentiate between several types of cyclone clustering and review multiple approaches used to quantify it. We provide an overview of current research activities including a review of serial cyclone clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 103 publications
1
41
0
1
Order By: Relevance
“…A number of previous studies have analysed the statistical properties of the serial clustering of extreme events. Mailier et al (2006), Vitolo et al (2009) and Pinto et al (2013) studied European winter storms (see Dacre and Pinto, 2020, for a review); Villarini et al (2011) quantified clustering of ex-treme precipitation in the North American Midwest;and Villarini et al (2012) focused on extreme flooding in Austria. In these studies, clustering in time was assessed using the index of dispersion (variance-to-mean ratio) of a one-dimensional homogeneous Poisson process model, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have analysed the statistical properties of the serial clustering of extreme events. Mailier et al (2006), Vitolo et al (2009) and Pinto et al (2013) studied European winter storms (see Dacre and Pinto, 2020, for a review); Villarini et al (2011) quantified clustering of ex-treme precipitation in the North American Midwest;and Villarini et al (2012) focused on extreme flooding in Austria. In these studies, clustering in time was assessed using the index of dispersion (variance-to-mean ratio) of a one-dimensional homogeneous Poisson process model, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Their study also indicated that reanalysis products are skilful in reproducing serial clustering identified in observations. Barton et al (2016) studied serial clustering of extreme precipitation events in southern Switzerland using Ripley's K function (Ripley, 1981) applied to a one-dimensional time axis (Dixon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Extratropical cyclones are one of the most important characteristics of mid-latitude climate of the Northern Hemisphere, as their passage is often associated with extreme weather conditions such as heavy precipitation and intense winds [1][2][3]. They are among the most severe weather phenomena that affect the western European countries and a common phenomenon during the boreal winter.…”
Section: Introductionmentioning
confidence: 99%
“…Previous climatic conditions or events such as persistent precipitation can produce soil saturation and increase the vulnerability of the system [24]. In many cases, when extreme weather events occur simultaneously or sequentially, they can overwhelm the ability of natural and human systems to cope, in turn creating social or environmental impacts [3]. The accumulated precipitation from several consecutive cyclones may cause rivers to overflow leading to flooding [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, this builds on previous research by extending the analysis of error growth to even larger scales, quantifying the impact of diabatic processes, and identifying methods for producing probabilistic forecasting when predictability is low. However, new expertise was also required, in topics including cyclone families [Dacre and Pinto (2020)], persistent weather regimes [Hauser et al (2020)], and new physical mechanisms such as interactions with the stratosphere [Kautz et al (2019)]. These new projects will also open new frontiers for collaboration with the seasonal and climate prediction communities, including valuable resources such as the new Subseasonal-to-Seasonal Prediction Project (S2S, WMO ( 2020)) and Subseasonal Experiment (SubX, NOAA (2020)) databases.…”
mentioning
confidence: 99%